1986
DOI: 10.1007/bf00006739
|View full text |Cite
|
Sign up to set email alerts
|

Effects of experimental flow regulation on invertebrate drift and stranding in the Flathead and Kootenai Rivers, Montana, USA

Abstract: Studies were conducted to determine the effects of experimental manipulations of discharge on invertebrate drift in two regulated rivers in northwestern Montana, USA. During these studies the discharge regime in the Flathead River was characterized by frequent flow fluctuations, while in the Kootenai River high discharge was maintained for much longer periods before flow was reduced to minimum discharge. The magnitude of the response of invertebrates to disturbance was different in the two rivers, in part beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
76
0
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(85 citation statements)
references
References 23 publications
8
76
0
1
Order By: Relevance
“…A key consequence of this conceptual model is that the absolute magnitude of hydraulic stress may be less important than its direction and rate of change in determining the response of invertebrate drift to flow variation (Imbert and Perry 2000). Empirical support for this model comes from drift observations during hydropeaking in regulated rivers, where differences in drift concentration between ascending and descending points along a hydrograph are regularly observed (Perry and Perry 1986;Patterson and Smokorowski 2011;Miller and Judson 2014).…”
Section: Hydraulic Effects On Drift Fluxmentioning
confidence: 99%
“…A key consequence of this conceptual model is that the absolute magnitude of hydraulic stress may be less important than its direction and rate of change in determining the response of invertebrate drift to flow variation (Imbert and Perry 2000). Empirical support for this model comes from drift observations during hydropeaking in regulated rivers, where differences in drift concentration between ascending and descending points along a hydrograph are regularly observed (Perry and Perry 1986;Patterson and Smokorowski 2011;Miller and Judson 2014).…”
Section: Hydraulic Effects On Drift Fluxmentioning
confidence: 99%
“…Associated reduction in streamflow resulting from changes in surface-and ground-water use greatly affects the suitability of a stream to sustain many types of aquatic fauna (Klein 1979). For example, fluctuations in streamflow and repeated exposure of areas along stream margins have been shown to result in slow recovery and decreased production of aquatic-macroinvertebrate assemblages (Perry andPerry 1986, Blinn et al 1995). Water withdrawals for agricultural, municipal, and other uses have been found to markedly reduce streamflow, resulting in a loss of habitat for stream biota (Postel 2000, McKay andKing 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Our long-term results corroborate these findings, since midges comprised a higher proportion of the macroinvertebrate community on substrates exposed for longer durations. Perry and Perry (1986) reported slower recovery of biotic communities in lotic ecosystems with daily fluctuations than in systems with less frequent fluctuations. Brusven et al (1974) suggested that prolonged dewatering of the Hell's Canyon reach of the Snake River reduced primary production, causing a lag in recolonization of invertebrates when conditions again became favorable.…”
Section: An Investigation Of Fluctuating Flows Downstream Of Dworshakmentioning
confidence: 97%
“…found appreciably higher stranding of invertebrates on dewatered substrate in the fall than spring, mainly because of their smaller size and reduced mobility in the fall. Perry and Perry (1986) found that more insects were stranded during a faster rate of decrease in discharge. Our exposure tests were artificially created, thus dewatering occurred much faster than the hydropeaking-induced changes in discharge and subsequent dewatered substrates.…”
Section: Artificial Exposuresmentioning
confidence: 99%
See 1 more Smart Citation